Oncostatin M [OSM] protein immuno-expression in oral squamous cell carcinoma – A prospective study - Sunil Prakash; Nandhini Gunasekaran; Ramya Mahalingam; Rajkumar Krishnan (Oral Oncology Reports)
Background: An important factor in the progression of tumours is the formation of blood vessels in the tumour stroma. When there is an upregulation of angiogenesis stimulators or a downregulation of angiogenesis inhibitors, the tumour may manifest its capacity for angiogenesis. Immune cells secrete a substance called Oncostatin M (OSM), which has been linked to cancer angiogenesis and subsequent pathogenesis. This study is aimed to assess OSM expression in oral squamous cell carcinoma. Objective: To compare the intensity of expression of Oncostatin M [OSM] in normal oral mucosa and Oral Squamous Cell Carcinoma and to analyse their role in the disease progression by enhancing angiogenesis and metastasis. Materials and methods: The study analysed the expression of OSM with the immunohistochemical aid. The samples were treated with Anti-OSM polyclonal antibody and immunohistochemical staining was done using NovoLinkTM NovocastraTM Polymer Detection System (Leica Microsystems). Stained samples were categorized based on the staining percentage and staining intensity. Results: The comparison of staining percentage between the epithelium of control group and the OSCC group revealed that it was statistically significant [p value = 0.002685]. Similarly, the comparison of staining intensity [p value = 0.001202] and staining index [p value = 0.001817] between the control group and the OSCC group revealed that it was statistically significant. Conclusion: The expression of oncostatin M in normal epithelium and OSCC group with the given immunohistochemical staining percentage, intensity and staining index suggests strong diagnostic potential of oncostatin M which can also be used for further therapeutic.